2019
DOI: 10.1021/acs.jctc.9b00346
|View full text |Cite
|
Sign up to set email alerts
|

Probing Molecular Chirality by Orbital-Angular-Momentum-Carrying X-ray Pulses

Abstract: A twisted X-ray beam with orbital angular momentum is employed in a theoretical study to probe molecular chirality. A nonlocal response description of the matter-field coupling is adopted to account for the field short wavelength and the structured spatial profile. We use the minimal-coupling Hamiltonian, which implicitly takes into account the multipole contributions to all orders. The combined interactions of the spin and orbital angular momentum of the X-ray beam give rise to circular-helical dichroism sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 71 publications
(91 reference statements)
1
35
0
Order By: Relevance
“…12 The question of how the OAM of vortex beam might engage with chiral object is a topic of resurgent interest. [13][14][15][16][17][18][19][20][21][22] The initial studies concluded that the OAM played no role in chiral light-matter interactions, [13][14][15] while the recent studies through OAM dichroism have shown that the OAM can produce chiroptical influence. [17][18][19][20][21] Since weak interactions between molecules and probing light, the common OAM and SAM dichrosim measurements are often challenging and cannot distinguish chirality information of individual molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The question of how the OAM of vortex beam might engage with chiral object is a topic of resurgent interest. [13][14][15][16][17][18][19][20][21][22] The initial studies concluded that the OAM played no role in chiral light-matter interactions, [13][14][15] while the recent studies through OAM dichroism have shown that the OAM can produce chiroptical influence. [17][18][19][20][21] Since weak interactions between molecules and probing light, the common OAM and SAM dichrosim measurements are often challenging and cannot distinguish chirality information of individual molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] The initial studies concluded that the OAM played no role in chiral light-matter interactions, [13][14][15] while the recent studies through OAM dichroism have shown that the OAM can produce chiroptical influence. [17][18][19][20][21] Since weak interactions between molecules and probing light, the common OAM and SAM dichrosim measurements are often challenging and cannot distinguish chirality information of individual molecule. In recent years, optical forces on chiral objects have attracted considerable attention not only for the optical separation of enantiomers but also for the further identification of chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Broadening the definition of "circular dichroism," fundamentally related effects have been identified in nonchiral nanostructures [30]; effects of a similar kind have also been discovered in achiral atomic matter [31] and chiral mesostructures [32], and they have been utilized in the characterization of material chirality [33] and spectroscopic probes of magnetism [34]. Other studies have investigated the exploitation of plasmonic coupling in material interactions with twisted light to engineer chiroptical effects [35][36][37][38][39][40], and recent theoretical work has predicted an x-ray analog to the CVD effect [41].…”
Section: Introductionmentioning
confidence: 99%
“…While understanding chiral interactions and timeresolving chiral electronic or vibronic dynamics are much desired, most of the existing ultrafast methods are restricted to weak interactions with the magnetic component of the light field (e.g. [27][28][29][30][31][32][33][34][35][36]). In the IR-VUV range, such restriction severely limits their efficiency for medium-size molecules or chiral moieties, with useful time-resolved signals often just above the noise [30][31][32][33][34].…”
mentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36]). In the IR-VUV range, such restriction severely limits their efficiency for medium-size molecules or chiral moieties, with useful time-resolved signals often just above the noise [30][31][32][33][34]. A recent experiment [33] graphically demonstrates the challenges: the time-resolved CD signal is only a few percent of the static CD and is on the order of the baseline stability of the setup.…”
mentioning
confidence: 99%